2008
DOI: 10.1016/j.tetlet.2007.12.105
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I) tetrafluoroborate as a potent promoter for chemical glycosylation

Abstract: We have identified silver tetrafluoroborate (AgBF 4 ) as an excellent promoter for the activation of various glycosyl donors including glycosyl halides, trichloroacetimidates, thioimidates, etc. Easy handling and no requirement for azeotropic dehydration prior to application makes AgBF 4 especially beneficial in comparison to the commonly used AgOTf. Selective activation of glycosyl halides or thioimidates over thioglycosides or n-pentenyl glycosides, including simple sequential one-pot syntheses, has been als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…While the syntheses of hexoses were accomplished from acetobromosugar and the corresponding sodium thiolates in MeCN, the synthesis of thioribofuranoside derivative was accomplished from the corresponding tetraacetate and trimethylsilylated thiols in the presence of TMSOTf [54]. The synthesis of a range of differently protected SBaz derivatives from the corresponding glycosyl bromides and KSBaz in acetone has also been reported [55]. …”
Section: S-benzothiazolyl Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…While the syntheses of hexoses were accomplished from acetobromosugar and the corresponding sodium thiolates in MeCN, the synthesis of thioribofuranoside derivative was accomplished from the corresponding tetraacetate and trimethylsilylated thiols in the presence of TMSOTf [54]. The synthesis of a range of differently protected SBaz derivatives from the corresponding glycosyl bromides and KSBaz in acetone has also been reported [55]. …”
Section: S-benzothiazolyl Derivativesmentioning
confidence: 99%
“…As an example, AgOTf-promoted glycosylation of diacetone galactose acceptor (6-OH) with glycosyl donors of the L-arabino, D-ribo, and D-xylo series in toluene afforded the corresponding disaccharides in 75% (α/β = 4/3), 98% (α/β = 7/2), and 70% (α/β = 3/10) yield, respectively. It was also reported that the SBaz leaving group can be very rapidly activated for glycosylation in the presence of AgBF 4 and is applicable to selective activation over other types of leaving groups involving S -alkyl and O -pentenyl glycosides [55]. It was also observed that the SBaz leaving group can be activated in the presence of MeOTf, but not in the presence of weaker alkylating reagents, which created a basis for selective activation of STaz donors with benzyl bromide or methyl iodide in the presence of glycosyl acceptors equipped with SBaz anomeric group [35].…”
Section: S-benzothiazolyl Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the wide range of biological interest in these compounds, this study pursues a mild, efficient and expedient protocol for synthesizing bisindolylmethanes. Silver tetrafluoroborate is a fluorodesulfurization reagent; 57 is used in the synthesis of 1,6-diketones from siloxycyclopropanes; 58 is a potent promoter of chemical glycosylation; 59 causes the silver ion-induced rearrangement of N-chloramines; 60 causes the silver-induced allylation of b-bromo ethers with allylsilanes, 61 and has other im-portant uses. Biffis et al reported the AgBF 4 -NHC carbene complexes induced the reaction between indoles and ethyl phenylpropiolate to produce diaddition product.…”
mentioning
confidence: 99%